KONFLIK INTERNAL TOKOH UTAMA DALAM MIMPI KECIL TITA KARYA DESI PUSPITASARI - Syifa Fauzia Chairul; Darsita Darsita Suparno; Santje Iroth; Donald Matheos Rattu (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2021)
Abstract: Many experts have observed the main character's internal conflict, however their analysis has not explained the conflict form that has an impact on the mental state of the child.  This study aims to analyze: a) form of inner conflict experienced by the main character in the novel Mimpi Kecil Tita, b) find out what factors cause internal conflict in the novel Mimpi Kecil Tita?  Sigmund Freud’s Psychoanalytic theory is used to reveal internal conflict and several factors that cause it.  Descriptive qualitative analysis was used as a research method. Overall, these results indicate that fears, anxiety, absence, and hopes are identified as conflict settings referring to the concepts of approach-avoidance and avoidance-avoidance. Viewed from the concept of approaching-avoidance (approach-avoidance) and broad-away (avoidance-avoidance) refers to anxiety, failure, pain, cunning based on the impact of personality or id.  The facts of the story show the Ego is miserable. This misery causes an inner conflict is identified as the avoidance of desire (approach-avoidance) marked by the confused id.  The form of Superego conflict in Tita is feelings of suffering, anger at someone, and hurt.  Four factors that cause internal conflict, namely economic hardship, dishonesty, frustration, and hurt feelings.Abstrak: Penelitian yang mengkaji konflik internal tokoh utama telah banyak dilakukan para ahli, namun analisis mereka terhadap konflik internal tokoh utama belum menjelaskan bentuk konflik yang berdampak pada keadaan jiwa anak. Teori Psikoanalis dari Freud digunakan untuk mengungkap tikai batin dan aneka faktor penyebab konflik. Analisis kualitatif deskriptif digunakan sebagai metode penelitian.  Secara keseluruhan, hasil ini menunjukkan ketakutan, kegalauan, ketiadaan, dan berharap diidentifikasi sebagai tatanan konflik merujuk kepada konsep mendekat-menjauh (approach-avoidance), dan konflik menjauh-menjauh (avoidance-avoidance). Ditinjau dari konsep mendekat-menjauh (approach-avoidance) dan menjauh-menjauh (avoidance-avoidance) merujuk kepada kecemasan, kegagalan, kepedihan, kelicikan didasarkan adanya dampak personalitas atau id. Fakta cerita menunjukkan Ego sengsara. Kesengsaraan itu menimbulkan konflik batin yang diidentifikasi sebagai penghindaran diri dari keinginan (appproach-avoidance) ditandai oleh id yang merasa kebingungan. Wujud konflik superego dalam diri Tita adalah perasaan penderitaan, marah pada seseorang, dan sakit hati. Faktor-faktor yang menimbulkan konflik internal ada empat yaitu kesulitan ekonomi, ketidakjujuran, frustasi, dan sakit hati.